Pembuatan Bioetanol Dari Kulit Nenas Menggunakan Enzim Selulase Dan Yeast Saccharomyces Cerevisiae Dengan Proses Simultaneous Sacharificatian And Fermentation (SSF) Terhadap Variasi Konsentrasi Inokulum Dan Waktu Fermentasi - Dwi Laura Pramita; Elvi Yenie; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
One of potential material that could be the raw material of bioethanol is pineapple peels. Pineapple peels is one of the biggest agricultural wastes in Indonesia, especially for Riau Province. Pineapple peels could be raw material for bioethanol production due to contains of fiber, carbohydrate and glucose. The purposes of this research are for making bioethanol from pineapple peel by using Simultaneous Sacharification and Fermentation Process (SSF) for finding the maximum inoculums concentration and the best time for fermentation process. The variations of inoculums are 5%, 7%, 10%, 12% and 15%. Then the variations for fermentation time are 2, 3, 4 and 5 days. The consists of bioethanol were tested by using alcoholmeter. From this research, the highest value of bioethanol is 14% or equal to 110,502 mg/ml, for variations at 10% inoculums and 4 days fermentation process. Keyword: Bioethanol; Pineapple peels; Saccharomyces Cerevisiae; Cellulose; SSF